Physiological and biochemical responses of thyme plants to some antioxidants - SALWA A. ORABI; IMAN M. TALAAT; LAILA K. BALBAA (Smujo International, 2014)
Abstract. Orabi SA, Talaat IM, Balbaa LK. 2014. Physiological and biochemical responses of thyme plants to some antioxidants. Nusantara Bioscience 6: 118-125. Two pot experiments were conducted to investigate the effect of tryptophan, nicotinamide and ?-tocopherol (each at 50 and 100 mg/L) on plant growth, essential oil yield, and its main constituents. All treatments significantly promoted plant height, and increased fresh and dry mass (g/plant) of thyme (Thymus vulgaris L.). The treatment with 100 mg/L nicotinamide showed increases in total potassium mainly in the first cut. Total soluble sugars, oil percentage, and oil yield and protein recorded increments with tryptophan treatments. Treatment of Thymus plants with 100 mg/L nicotinamide observed the highest percentage of thymol (67.61%). Oxygenated compounds recorded the highest value with 50 mg/L ?-tocopherol treatment, while the maximum non-oxygenated ones resulted from the application of 100 mg/L nicotinamide. All treatments under study significantly affected the activity of oxidoreductase enzymes (POX and PPO). Nicotinamide at the concentration of 100 mg/L recorded the highest increments in APX and GR and the lowest values in oxidoreductase enzyme activities added to the lowest values of lipid peroxidation to enhance the best protection of thyme plants.